2018
DOI: 10.1016/j.apergo.2018.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient of friction testing parameters influence the prediction of human slips

Abstract: Measuring the available coefficient of friction (ACOF) of a shoe-floor interface is influenced by the choice of normal force, shoe-floor angle and sliding speed. The purpose of this study was to quantify the quality of slip prediction models based on ACOF values measured across different testing conditions. A dynamic ACOF measurement device that tests entire footwear specimens (Portable Slip Simulator) was used. The ACOF was measured for nine different footwear-contaminant combinations with two levels of norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…This occurrence altered the applied normal force, outside of the 250 ± 25 N range. The loading conditions used in this study were selected because they are consistent with the heel dynamics during slip initiation (Jones et al, 2018), are predictive of slipping (A. Iraqi, Cham, R., Redfern, M.S., Beschorner, K.E., 2018), and are part of a draft standard for shoe friction that is currently being considered (ANSI/NFSI B101.7-2018).…”
Section: Methodsmentioning
confidence: 99%
“…This occurrence altered the applied normal force, outside of the 250 ± 25 N range. The loading conditions used in this study were selected because they are consistent with the heel dynamics during slip initiation (Jones et al, 2018), are predictive of slipping (A. Iraqi, Cham, R., Redfern, M.S., Beschorner, K.E., 2018), and are part of a draft standard for shoe friction that is currently being considered (ANSI/NFSI B101.7-2018).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, ACOF measurements are affected by shoe-floor angle (Beschorner et al, 2007; Blanchette and Powers, 2015b), vertical force (Beschorner et al, 2007; Blanchette and Powers, 2015b), horizontal sliding speed (Beschorner et al, 2007; Blanchette and Powers, 2015b; Redfern and Bidanda, 1994) and contact duration (Gronqvist et al, 2003). Prior research has suggested that using test conditions that are more biofidelic improves the ability of ACOF measurements to predict slips (Iraqi et al, 2018). Furthermore, other biomechanical parameters that have not been formally incorporated in ACOF testing may need to be considered to improve biofidelity.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research explores the relevance of COF testing, particularly concerning human ambulation and slip risk. 15,16,17,18,19 Notably, research by Iraqi, Cham, Redfern, and Beschorner (2018) 20 shows that COF can be used as a predictor of slip risk for same-level ambulation, indicating that available friction can have a significant effect on the potential for slip events while walking. Further, research conducted in Germany establishes a correlation between human ambulation and DCOF and provides a basis for the development of many laboratory and field DCOF test methods.…”
Section: Relevance Of Cof Testingmentioning
confidence: 99%
“…If the change in traction is unexpected, the change could result in a slip or fall. 47 Texture, surface roughness, and patterning in the flooring can cause directionality if more prevalent in one orientation. 48 Overall, directionality when wet was exhibited by six of the PBM products tested for this report, as determined by comparing measurements in one direction versus measurements at 90 degrees.…”
Section: Directionality Propertiesmentioning
confidence: 99%